Pengabdian Kepada Masyarakat Politeknik Mandiri Bina Prestasi Dalam Wisuda PAUD Dian Bersinar Foundation Medan - Diana, Sinta; Sianipar, Selvie; Harianja, Riodinar (Pengelola Jurnal Politeknik Negeri Ketapang Jl. Rangga Sentap, Dalong Sukaharja, Ketapang 78813. Telp. (0534) 3030686 Kalimantan Barat, 2021)
Dian Bersinar Foundation Medan is a non-profit (independent) foundation in advancing education through the provision of Early Childhood Education (PAUD) for children on the outskirts of the railroad tracks. the end of the learning program is carried out officially in an academic event in the form of graduation activities. The purpose of Community Service at the Mandiri Bina Prestasi Polytechnic in the graduation of the Dian Bersinar Foundation Early Childhood Education (PAUD) Medan is to provide services to the community that support the implementation of general government tasks through the provision of packages in the form of bags and several books as wellstationary.This assistance is expected to be an encouragement for PAUD students to continue their education to elementary school. This package was handed over to 12 early childhood children in the presence of the Dian Bersinar Foundation, Medan, the Mandiri Bina Prestasi Polytechnic Team (three lecturers and two students) and parents. The method used in this activity is the approach/persuasive method and observation. Based on observations before graduation, social workers are looking for donors to contribute to the graduation package. With the existence and active role of the Mandiri Bina Prestasi Polytechnic Medan, the graduation was carried out well and memorable because each child received a bag package. In the future, community service can be further developed in more tangible collaborations at the Dian Bersinar Foundation Medan, such as mentoring teaching and learning activities, training, and the arts.